Role of the State in Modernization and Development in Post-Colonial Sri Lanka. Conceptual perspectives - Vitharana, Sarath; Abeysinghe, Chaminda (Technium Social Sciences Journal, 2021)
The modernization and development of the post-colonial countries were associated with external and internal factors. Many argue that socio-economic, political, and constitutional reforms introduced by colonial masters during their rule have phenomenally contributed to the initiation of the modernization and development process by bringing liberal political-economic and governance reforms into the prevailed feudalist system. Moreover, even after the independence, the state apparatus designed and formed under the context of colonial inherence became a pivotal actor for determining modernization and development of the country. Thus this study examined the role of the Sri Lankan state in the modernization and development process in the post-colonial countries era. The study adopted secondary data and content analysis as a method of data collection. The study found that the state has played a significant role in modernization and socio-economic development in post-colonial developing countries. This study reveals that the states’ capacity and capability in the modernization and development process have diminished since the 1960s due to the lack of economic development performances in respective countries. Apart from that, economic reforms such as the neo-liberal economic reforms, which encourage the minimal-state policies introduced by the United National Party’s regime in 1977, also have caused the decline of state intervention in the Sri Lankan context. However, the public’s general view is that the state should further perform its duties and responsibilities vested with socio-economic development and modernization processes in these post-colonial countries.